2005
DOI: 10.1530/eje.1.01853
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and premature menopause: is their co-existence detrimental to the skeleton?

Abstract: Objective: Premature menopause is a known risk factor for osteoporosis, whilst the influence of type 2 diabetes on bone mineral density (BMD) is still controversial. Design and methods: BMD values assessed by dual-energy X-ray absorptiometry (DXA) in L2-L4 vertebrae and the femoral neck (FN) of 40 diabetic women with premature menopause (D-EMP) were compared with those of 60 non-diabetic, prematurely menopausal women (EMP) and 60 diabetic women with normal menopause (D-NMP) who had been matched by age and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Moreover, point biserial correlation and Ferguson's sigma values which are an item-total correlation and discriminatory power, respectively, were within the acceptable range and indicated that the tool is reliable and discriminating [23,32]. *Sum of the potential range for the Exercise subscale and Calcium intake subscale was larger than total potential range because the two subscales shared nine common questions (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed low correct answer frequencies for all dimension with low overall knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, point biserial correlation and Ferguson's sigma values which are an item-total correlation and discriminatory power, respectively, were within the acceptable range and indicated that the tool is reliable and discriminating [23,32]. *Sum of the potential range for the Exercise subscale and Calcium intake subscale was larger than total potential range because the two subscales shared nine common questions (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed low correct answer frequencies for all dimension with low overall knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a chronic metabolic disorder with substantial morbidity and mortality, and osteoporosis is a silent disease, also with harmful impact on morbidity and mortality [1, 20]. Osteoporosis leads to increase in skeletal fragility and microarchitecture deterioration of bone tissue with a decrease in bone mineral density (BMD), bone quality, and strength [9, 62].…”
Section: Other Diabetic Complicationsmentioning
confidence: 99%
“…Pharmacotherapy, continuing medical care, and education are crucial for preventing acute and chronic complications. On the other hand, osteoporosis (OP) is a painless weakening of the bones that constitutes an enormous socioeconomic crisis, with a harmful impact on morbidity and mortality 3,4. It leads to increased skeletal fragility and microarchitectural deterioration of bone tissue, causing a decrease in bone mineral density (BMD), bone quality, and strength 5,6.…”
Section: Introductionmentioning
confidence: 99%